Quantum key distribution network for multiple applications. (6th July 2017) - Tajima, A; Kondoh, T; Ochi, T; Fujiwara, M; Yoshino, K; Iizuka, H; Sakamoto, T; Tomita, A; Shimamura, E; Asami, S; Sasaki, M
Abstract: The fundamental architecture and functions of secure key management in a quantum key distribution (QKD) network with enhanced universal interfaces for smooth key sharing between arbitrary two nodes and enabling multiple secure communication applications are proposed. The proposed architecture consists of three layers: a quantum layer, key management layer and key supply layer. We explain the functions of each layer, the key formats in each layer and the key lifecycle for enabling a practical QKD network. A quantum key distribution-advanced encryption standard (QKD-AES) hybrid system and an encrypted smartphone system were developed as secure communication applications on our QKD network. The validity and usefulness of these systems were demonstrated on the Tokyo QKD Network testbed.